2012
DOI: 10.1007/s00122-012-1797-7
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of long staple fiber quality traits of Gossypium barbadense in G. hirsutum background using CSILs

Abstract: Gossypium hirsutum is a high yield cotton species that exhibits only moderate performance in fiber qualities. A promising but challenging approach to improving its phenotypes is interspecific introgression, the transfer of valuable traits or genes from the germplasm of another species such as G. barbadense, an important cultivated extra long staple cotton species. One set of chromosome segment introgression lines (CSILs) was developed, where TM-1, the genetic standard in G. hirsutum, was used as the recipient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 51 publications
4
71
0
Order By: Relevance
“…Hai7124 with a sea-island leaf and the recurrent parent G. hirsutum accession TM-1 ( Figure 1A). Although it is phenotypically a sea-island leaf plant (Wang et al 2012), the CSIL line is a near-isogenic line to TM-1. IL-15-5-1 was crossed as a male parent with TM-1 to produce a mapping population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hai7124 with a sea-island leaf and the recurrent parent G. hirsutum accession TM-1 ( Figure 1A). Although it is phenotypically a sea-island leaf plant (Wang et al 2012), the CSIL line is a near-isogenic line to TM-1. IL-15-5-1 was crossed as a male parent with TM-1 to produce a mapping population.…”
Section: Resultsmentioning
confidence: 99%
“…Eighty-nine accessions from seven races of G. hirsutum were listed in Table S2, provided by the Institute of Cotton Research of the Chinese Academy of Agricultural Sciences (CAAS). IL-15-5-1 was derived from a CSIL with sea-island leaves that carried the Hai7124 segment from chromosome D1 in the background of the recurrent parent TM-1 (Wang et al 2012). Two F 2 mapping populations of 770 and 508 individuals were developed from a cross between TM-1 as the female parent and IL-15-5-1 as the male parent.…”
Section: Plant Materials and Genotypingmentioning
confidence: 99%
“…Mapping populations are obtained using two contrasting parents for the desired trait. In self-pollinated crops; usually mapping populations include F 2 [56,57]; F 2:3 [58,59], recombinant inbred lines (RILs) [60,61], backcross (BC) [62,63], Backcross inbred lines (BILs) [64], near isogenic lines [65,66], doublehaploids [67,68], chromosome substitution lines (CSILs) [69,70]. F 2 , BC, RILs and doublehaploids have been highly used for linkage mapping studies in cotton.…”
Section: Mapping Populationmentioning
confidence: 99%
“…It is manifested by high heritability-ranged from 0.52 to 0.90 for fiber bundle strength and 0.46 to 0.79 for staple length [146][147][148][149]. Previous studies have shown that staple length is highly under the influence of the genotype [69]. In the present cultivated varieties, significantly low variations for the staple length were observed-thus hampering the future breeding progress because of low genetic diversity available for the trait [25,150,151].…”
Section: Staple Lengthmentioning
confidence: 99%
“…is cytogenetically subdivided, and based on meiotic compatibility, it is divided in eight genomic groups (A-G and K). Of the total species, only four were domesticated by humans to produce fiber: G. herbaceum L. (2n = 2x = 26), G. arboreum L. (2n = 2x = 26), G. hirsutum L. (2n = 4x = 52), and G. barbadense L. (2n = 4x = 52) (WANG et al, 2012).…”
Section: Introductionmentioning
confidence: 99%